Progress in Q-carbon and related materials with extraordinary properties. Issue 7 (3rd July 2018) - Narayan, Jagdish; Bhaumik, Anagh; Gupta, Siddharth; Haque, Ariful; Sachan, Ritesh
ABSTRACT: This paper summarizes our research related to Q-carbon and Q-BN and direct conversion of carbon into diamond and h-BN into c-BN. Synthesis and processing of these materials are accomplished by nanosecond laser melting and subsequent quenching of amorphous carbon and nanocrystalline h-BN. Depending upon the degree of undercooling, molten carbon (or h-BN) can be converted into Q-carbon (or Q-BN) or diamond (or c-BN). The primary focus here is on the outstanding properties of these materials, including hardness greater than diamond, ferromagnetism, p- and n- type doping, NV nanodiamonds, high-temperature superconductivity in B-doped Q-carbon, enhanced field emission, superhard composite coatings, and future applications. IMPACT STATEMENT This research represents a fundamental breakthrough in the direct conversion of carbon into diamond at ambient temperatures and pressures in the air and their extraordinary properties. GRAPHICAL ABSTRACT: